Paisagem arquitetônica da cidade de João Pessoa/PB e seu significado: o perceptivo dos moradores e visitantes - Bandeira, Sâmia érika Alves de Caldas (2011)
This study was conducted in the city of João Pessoa, Paraíba mesoregion Forest. Having to analyze how does the appreciation of the architectural heritage to the visitor and pessoense Capital Paraiba, taking into account the narratives of João Pessoa, and practitioners of foreign tourists of cultural tourism. This research builds on a theoretical foundation on concepts of landscape and place. Was taken as a foundation to Cultural Geography. The research in question is justified by embarking on Geography and Heritage and cast a glance on the geographical cultural landscape, trying to unravel the symbols assigned to the ancient architectural examples, meaning that interfere with power relationships that cross generations, constructing and deconstructing identities, is dispersed or integrating cultures, creating cultural groups and social conflict. It is concluded that the geographical area derives from a number of factors, among them the culture and this in turn will shaping the landscape, reflecting the abstract over the concrete architecture of the oldest to the most current, turning from the material to the immaterial in World Heritage Site